2014
DOI: 10.7554/elife.04132
|View full text |Cite
|
Sign up to set email alerts
|

A stress assembly that confers cell viability by preserving ERES components during amino-acid starvation

Abstract: Nutritional restriction leads to protein translation attenuation that results in the storage and degradation of free mRNAs in cytoplasmic assemblies. In this study, we show in Drosophila S2 cells that amino-acid starvation also leads to the inhibition of another major anabolic pathway, the protein transport through the secretory pathway, and to the formation of a novel reversible non-membrane bound stress assembly, the Sec body that incorporates components of the ER exit sites. Sec body formation does not depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
166
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(175 citation statements)
references
References 62 publications
9
166
0
Order By: Relevance
“…a strict COPII-dependent emergence of a secretory flux. Although this study focused the role of mitogens in regulating ERES, others have recently identified in Drosophila a novel response of ERES to amino acid starvation (Zacharogianni et al, 2014), which is distinct from the response to serum starvation reported previously (Zacharogianni et al, 2011). Amino acid starvation results in the formation of 'Sec bodies', where Sec16 and other COPII components are stored.…”
Section: Discussionmentioning
confidence: 99%
“…a strict COPII-dependent emergence of a secretory flux. Although this study focused the role of mitogens in regulating ERES, others have recently identified in Drosophila a novel response of ERES to amino acid starvation (Zacharogianni et al, 2014), which is distinct from the response to serum starvation reported previously (Zacharogianni et al, 2011). Amino acid starvation results in the formation of 'Sec bodies', where Sec16 and other COPII components are stored.…”
Section: Discussionmentioning
confidence: 99%
“…These dynamic properties of organelles are essential for normal cellular functions, being critical in development (Hanna et al, 2013), differentiation (Forni et al, 2016), mitosis (Jongsma et al, 2015), and various forms of stress response (Farber-Katz et al, 2014; Zacharogianni et al, 2014). Consequently, organelle dysfunction is known to be the driver of severe human diseases, including disorders of the mitochondria (Reeve et al, 2013), endoplasmic reticulum (ER) (Kerbiriou et al, 2007), endosomes (Cataldo et al, 2008), lysosomes (Platt et al, 2012), and peroxisomes (Smith and Aitchison, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We then used them to follow PARylation and MARylation in vivo during cellular stresses, with particular focus on amino-acid starvation that induces the formation of a recently described stress assembly, the Sec body (Zacharogianni et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Sec body formation results from the inhibition of a major anabolic pathway, the protein transport through the secretory pathway, upon amino-acid starvation of Drosophila cells (Amodio et al, 2009; Zacharogianni et al, 2014). The secretory pathway ensures the delivery of signal peptide containing proteins to the extracellular medium and the plasma membrane and to nearly all membrane-bound compartments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation